2018
DOI: 10.1002/lipd.12040
|View full text |Cite
|
Sign up to set email alerts
|

Previous Gestational Diabetes Increases Atherogenic Dyslipidemia in Subsequent Pregnancy and Postpartum

Abstract: In a cohort of women with previous gestational diabetes mellitus (GDM), we aimed to ascertain whether women with abnormal glucose tolerance 1-year postdelivery had a more atherogenic lipid profile during and after pregnancy than those with normal glucose tolerance. A prospective cohort study with longitudinal design between January 2004 and March 2016 was conducted. Three hundred and six (56.8%) of 537 women diagnosed with GDM during the studied period attended a control visit during the first year after deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
3
6
0
Order By: Relevance
“…The present findings indicated that lipid levels during pregnancy were associated with an increased risk of dyslipidemia after delivery. This finding is consistent with two other studies that also showed a relationship between hypertriglyceridemia in pregnancy and at 6-12 months postpartum [25,26].…”
Section: Discussionsupporting
confidence: 93%
“…The present findings indicated that lipid levels during pregnancy were associated with an increased risk of dyslipidemia after delivery. This finding is consistent with two other studies that also showed a relationship between hypertriglyceridemia in pregnancy and at 6-12 months postpartum [25,26].…”
Section: Discussionsupporting
confidence: 93%
“…The present ndings indicated that lipid levels during pregnancy were associated with an increased risk of dyslipidemia after delivery. This nding is consistent with two other studies that also showed a relationship between hypertriglyceridemia in pregnancy and at 6-12 months postpartum [25,26].…”
Section: Discussionsupporting
confidence: 93%
“…When LDL-C was combined with age, SBP and HbA1c, the AUC reached to 0.733. The present ndings indicated that lipids levels during pregnancy were associated with increased risk of dyslipidemia after delivery which was consistent with two other studies that also presented the relationship between hypertriglyceridemia in pregnancy and 6 to 12 months postpartum [22,23] .…”
Section: Discussionsupporting
confidence: 93%